2014
DOI: 10.2147/ijgm.s64096
|View full text |Cite
|
Sign up to set email alerts
|

Motives for mixing alcohol with energy drinks and other nonalcoholic beverages, and consequences for overall alcohol consumption

Abstract: IntroductionThe aim of this survey was to assess the motives for energy drink consumption, both alone and mixed with alcohol, and to determine whether negative or neutral motives for consuming alcohol mixed with energy drinks (AMED) have a differential effect on overall alcohol consumption.MethodsDemographics, alcohol and energy drink consumption-related questions, and motives for the consumption of energy drinks (alone or mixed with alcohol) were assessed. The motives to mix alcohol with energy drinks were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…This study identified classes of consumers motivated by factors associated with taste preference, energy seeking, hedonism, and intoxication-related outcomes, reflecting those identified in previous studies (Droste et al, 2014;Marczinski, 2011;O'Brien et al, 2008b;Peacock et al, 2013;Verster et al, 2014). It is important to note that some consumers endorsed all motives, while others endorsed just 1 or 2.…”
Section: Discussionsupporting
confidence: 80%
“…This study identified classes of consumers motivated by factors associated with taste preference, energy seeking, hedonism, and intoxication-related outcomes, reflecting those identified in previous studies (Droste et al, 2014;Marczinski, 2011;O'Brien et al, 2008b;Peacock et al, 2013;Verster et al, 2014). It is important to note that some consumers endorsed all motives, while others endorsed just 1 or 2.…”
Section: Discussionsupporting
confidence: 80%
“…Eight studies used a within‐subject design to compare alcohol consumption on a typical AMED and a typical AO occasion (Brache & Stockwell, ; De Haan et al, ; Johnson, Alford, Stewart, et al, ; Lubman et al, ; Peacock, Bruno, & Martin, ; Price, Hilchey, Darredeau, Fulton, & Barrett, Verster et al, ; Woolsey et al, ). Alcohol intake of 3,480 AMED consumers was compared for both occasions.…”
Section: Resultsmentioning
confidence: 99%
“…In the Netherlands, Verster et al () compared alcohol consumption of 1,239 AMED consumers on occasions when they consumed AMED with occasions when they mixed alcohol with other nonalcoholic beverages (AMOB). Overall, the motives for consuming AMED and AMOB were similar.…”
Section: Resultsmentioning
confidence: 99%
“…Energy drinks are non‐alcoholic beverages which often contain ingredients, such as caffeine, taurine, and B‐vitamins. Important reasons for consuming energy drinks, other than people liking the taste, are the effects of caffeine on reducing sleepiness and improving alertness and concentration (Verster et al ., ).…”
Section: Introductionmentioning
confidence: 97%